2020
DOI: 10.1038/s41598-020-60154-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual mechanisms of social affiliation in zebrafish

Abstract: Elementary cues of biological motion elicit approach in zebrafish. Biologic motion can be decomposed into elementary animacy cues, such as changes in acceleration 35 and start from rest, which indicates that there is an internal energy source that initiates the motion (aka self-propulsion) 36. Newly hatched chicks and humans, although distant-related species, are both able to perceive these elementary cues of animacy when simple geometric forms are used (e.g. single dot). Such stimuli elicits affiliative behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 59 publications
3
53
0
Order By: Relevance
“…Oxytocin receptor mutant zebrafish, Danio rerio , line ( oxtr −/− ), raised in a TL‐mixed background, were generated in the laboratory of Dr Gil Levkowitz (Weizmann Institute of Science) using a transcription activator‐like effector nuclease (TALEN) genome‐editing tool. Our previous data showed that mutant oxtr (−/−) fish exhibit an impaired oxytocinergic signalling (validation of the line in Nunes et al). Zebrafish genotyping was performed according with the procedure described by Blechamnn et al.…”
Section: Methodsmentioning
confidence: 99%
“…Oxytocin receptor mutant zebrafish, Danio rerio , line ( oxtr −/− ), raised in a TL‐mixed background, were generated in the laboratory of Dr Gil Levkowitz (Weizmann Institute of Science) using a transcription activator‐like effector nuclease (TALEN) genome‐editing tool. Our previous data showed that mutant oxtr (−/−) fish exhibit an impaired oxytocinergic signalling (validation of the line in Nunes et al). Zebrafish genotyping was performed according with the procedure described by Blechamnn et al.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, a crucial difference between the present and earlier studies was that we presented videos rather than still images, allowing us to incorporate information about movement. Our own laboratory showed dogs are attracted by the motion of a laterally walking dog (Eatherington et al 2019) and studies in other species highlight how motion cues alone can be used for the recognition of conspecifics (Jitsumori et al 1999;Nunes et al 2020). Thus, the presence of motion information in our experiment may have played a role in allowing dogs to appropriately identify the conspecific's video.…”
Section: Discussionmentioning
confidence: 65%
“…OXTR mutant zebrafish line (ZFIN ID: ZDB-ALT-190830–1) was generated and provided by Dr. Gil Levkowitz (Weizmann Institute of Science) using a TALEN-based genome editing system. The characterization of this line has been described in Nunes et al, 2020 .…”
Section: Methodsmentioning
confidence: 99%